Laser-Combined Scanning Tunneling Microscopy on the Carrier Dynamics in Low-Temperature-Grown GaAs/AlGaAs/GaAs. (22nd November 2011) - Terada, Yasuhiko; Yoshida, Shoji; Takeuchi, Osamu; Shigekawa, Hidemi
Abstract : We investigated carrier recombination dynamics in a low-temperature-grown GaAs (LT-GaAs)/AlGaAs/GaAs heterostructure by laser-combined scanning tunneling microscopy, shaken-pulse-pair-excited STM (SPPX-STM). With the AlGaAs interlayer as a barrier against the flow of photocarriers, recombination lifetimes in LT-GaAs of 4.0 ps and GaAs of 4.8 ns were successfully observed separately. We directly demonstrated the high temporal resolution of SPPX-STM by showing the recombination lifetime of carriers in LT-GaAs (4.0 ps) in the range of subpicosecond temporal resolution. In the carrier-lifetime-mapping measurement, a blurring of recombination lifetime up to 50 nm was observed at the LT-GaAs/AlGaAs boundary, which was discussed in consideration of the screening length of the electric field from the STM probe. The effect of the built-in potential on the signal, caused by the existence of LT-GaAs/AlGaAs/GaAs boundaries, was discussed in detail.